Sistematicidad y técnica legislativa en materia penal: un estudio a partir de los delitos nucleares de la Ley de Tránsito chilena - Mayer Lux, Laura (2022)
The objective of this paper is to examine the principle of systematicity as a criterion of an adequate legislative technique in criminal matters, regarding the norms that regulate nuclear crimes of vehicular traffic in Chile. The analysis focuses on the rule that establishes the effective enforcement of the custodial sentences imposed on some of these crimes, which breaks with the system of crimes regulated in Chile, that is generally based on another class of criminal reactions. The study uses fundamentally a dogmatic methodology and a recourse to legal, jurisprudential and doctrinal sources. Among its results, the article highlights the relevance that the principle of systematicity has for the creation of criminal laws, either as such or in relation to other principles of law, like equality before the law, proportionality or certainty. It also concludes that the violation of the principle of systematicity affects both formal and substantive aspects, that is, relative to the instruments that serve as a source for criminal norms and their content.